Technologies of transformation: The end of the social or the birth of the cyber network? - Pertierra, Raul (Animo Repository, 2009)
This paper examines some of the claims about the transformative consequences of new communicative media, especially as they apply to the Philippines. Modern technologies were introduced into the country soon after their discovery abroad but despite their transformative potential there was very little change in the basic structures of society. Why was this so? The transformative capacity of technology has been the driving force for social change in modern times. Why has the Philippines remained a conservative society unable to harness the potentials of technology despite its rapid introduction into the country? Are there cultural reasons for this social conservatism? Will the mobile revolution finally transform the Philippines into a technologically driven economy and society?